2009
DOI: 10.1242/jeb.029884
|View full text |Cite
|
Sign up to set email alerts
|

Barnacle cement: a polymerization model based on evolutionary concepts

Abstract: SUMMARYEnzymes and biochemical mechanisms essential to survival are under extreme selective pressure and are highly conserved through evolutionary time. We applied this evolutionary concept to barnacle cement polymerization, a process critical to barnacle fitness that involves aggregation and cross-linking of proteins. The biochemical mechanisms of cement polymerization remain largely unknown. We hypothesized that this process is biochemically similar to blood clotting, a critical physiological response that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 78 publications
11
135
0
1
Order By: Relevance
“…The protein contents of barnacle cement has been the topic of considerable research as of late (Kamino 2001;Mori et al 2007;Urushida et al 2007;Kamino 2008;Dickinson et al 2009) yet few cement proteins have been added to the database (19kDa, 20kDa, and 100kDa as well as insoluble partial peptide fractions). Although many were collected from a different, though similar species, Megabalanus rosa, we were consequently hopeful in identifying similar cement polymers on the basis that partial sequence data may be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein contents of barnacle cement has been the topic of considerable research as of late (Kamino 2001;Mori et al 2007;Urushida et al 2007;Kamino 2008;Dickinson et al 2009) yet few cement proteins have been added to the database (19kDa, 20kDa, and 100kDa as well as insoluble partial peptide fractions). Although many were collected from a different, though similar species, Megabalanus rosa, we were consequently hopeful in identifying similar cement polymers on the basis that partial sequence data may be used.…”
Section: Discussionmentioning
confidence: 99%
“…This droplet was quickly collected into a 20µl pipette tip and immediately placed into rehydration buffer (described below). Due to the difficulty of this protein collection method, as described by recent fouling research Dickinson et al 2009), samples from one to three barnacles were pooled giving a maximum of 5µl and minimum of 3µl cement volume per gel. I collected cement from barnacles from both temperature treatments to create four replicates within each treatment.…”
Section: Cement Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the adhesive cures is still not fully understood. Recent work of Dickinson et al [14] suggested that cement polymerization may be a specialized form of wound healing similar to blood clotting. The structure of the thin (approx.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the thin (approx. 1 mm) adhesive layer has been shown to be a fibrillar [14][15][16][17] protein with secondary structure exhibiting characteristics of amyloid-folded (antiparallel b-sheet) proteins in Balanus amphitrite [17]. Above the proteinaceous cement layer in many barnacles is a calcified base plate, imparting further mechanical rigidity to the adhesive interface.…”
Section: Introductionmentioning
confidence: 99%